SIFAT FISIK KAYU LAPIS BERBAHAN BAKU KAYU AKASIA (Acacia mangium Willd) DAN KELAMPAYAN (Anthocephalu spp) - Arsad, Effendi (Jurnal Riset Industri Hasil Hutan, 2011)
The utilization of acacia and kelampayan wood asÂ  plywood materialsÂ  were done. There are two kinds of treatments with two cores samples.Â  Wood core with thickness 2 mm and 3 mm with the spreading rate of adhesiveÂ  150 gr/m2, 200 gr/m2 and 250 gr/m2. Â Â Resuls showedÂ  that theÂ  water contentÂ  of plywoodÂ  are 9,01% - 14,29%Â  for acacia and 9,17% - 10,58%Â Â  for kelampayan wood material.Â  The density of the plywood are 0,62 gr/cm3 â 0,73 gr/cm3 Â for acacia and 0,44 gr/cm3 â 0,57 gr/cm3.Â  for kelampayan wood material.Â  The tensileÂ  strength of plywood are tensile strength ofÂ  plywoodÂ  are 9,49 kg/cm2 â 14,73 kg/cm2 Â for acacia and 8,61 kg/cm2 â 12,58 kg/cm2Â  Â for kelampayan wood material.Keywords: acacia, kelampayan, Â the spreading rate of adhesive, Â physicsÂ Â Â Â Â Â  characteristic,Â  plywood